Understanding the Increasing Role and Value of the Professional Case Manager: A National Study From the Commission for Case Manager Certification. Issue 3 (May 2020) - Tahan, Hussein M.; Kurland, MaryBeth; Baker, Michelle
Abstract : Purpose: The purpose of the national role and function study was to identify the essential activities and necessary knowledge areas for effective professional case management practice from the perspective of those currently functioning in such roles in various care settings and across diverse professional disciplines. Primary Practice Settings: The national study covered the diverse case management practices and/or work settings across the full continuum of health and human services. Methodology and Sample: This cross-sectional descriptive study used the practice analysis method and online survey research design. It employed a purposive sample of case managers, in which an open participation link was e-mailed to nearly 60, 000 case managers, both certified and not yet certified. A total of 5, 416 responses were received, of which 2, 810 were found to be acceptable for consideration in the study. A representative group of individuals engaged in case management completed the survey in sufficient numbers to meet the requirements for conducting meaningful statistical analyses including subgroup comparisons. Results: The study identified the common activities (6 domains) and knowledge areas (5 domains) necessary for competent and effective performance by professional case managers, as highlighted in this article, which is the first of a 2-part series on the 2019 role and function study. The results informed the needed update of the test specifications for the Certified Case Manager (CCM) certification examination, as will be delineated in Part II of this article series. The update was necessary because case management practice has continued to evolve and to ensure the examination reflects current practices. Implications for Case Management Practice: The study identified essential activities and knowledge topics at both the micro- and macro levels that define competent and effective professional case management practice, also referred to as the substantive evidence of practice. It helps keep the CCM credentialing examination evidence-based and maintain its validity for evaluating the competency of professional case managers. In addition, the findings document how the practice has evolved over the past 5 years since the conduct of the last national study. Moreover, findings inform the development of programs and curricula for the training and advancement of case managers. The study instrument also is beneficial for further research into professional case management practice—most importantly linking the roles and functions of case managers to client care outcomes.